SOSIALISASI ARTI PENTING DAN STRATEGI PENGUATAN MEREK KOPI LOKAL “GUNUNG CIREMAI” UNTUK MENINGKATKAN OMSET PENJUALAN - Wachdijono, Wachdijono; Jaeroni, Akhmad (Universitas Djuanda, 2021)
ABSTRACTIn fact, it shows that finding local brand coffee drinks is more difficult than non-local brands. This is related to the position of the product brand in the market. If the position is very strong, the products will still exist and be easily found everywhere. This Community Service activity aims to disseminate the importance of the brand and strategies / efforts to strengthen the local coffee product brand